1996
DOI: 10.1128/jb.178.23.6882-6887.1996
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-independent bacterial chemoresponses correlate with changes in the cytoplasmic level of fumarate

Abstract: Bacterial chemotaxis is based on modulation of the probability to switch the direction of flagellar rotation. Responses to many stimuli are transduced by a two-component system via reversible phosphorylation of CheY, a small cytoplasmic protein that directly interacts with the switch complex at the flagellar motor. We found that the chemorepellents indole and benzoate induce motor switching in Escherichia coli cells with a disabled phosphorylation cascade. This phosphorylation-independent chemoresponse is expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…In general, however, when comparing results from chemotaxis assays performed under different conditions, it is worth noting that there are factors that can affect motor behavior independently of CheY phosphorylation (Khan and Macnab, 1980;Montrone et al, 1996;Turner et al, 1996;Barak et al, 1998).…”
Section: Behavioral Assaysmentioning
confidence: 99%
“…In general, however, when comparing results from chemotaxis assays performed under different conditions, it is worth noting that there are factors that can affect motor behavior independently of CheY phosphorylation (Khan and Macnab, 1980;Montrone et al, 1996;Turner et al, 1996;Barak et al, 1998).…”
Section: Behavioral Assaysmentioning
confidence: 99%
“…The response to other attractants was lower, but this could be a result of non-optimal concentrations of the attractants. Interestingly, even benzoate and acetate, which are repellents for wild-type E. coli , increased the probability of CCW rotation at 10 ¹5 M. [At millimolar concentrations, benzoate (Montrone et al, 1996) and acetate (Wolfe et al, 1988) decrease the probability of CCW rotation in Y þ -gutted strains.] The other repellents tested, indole, Ni 2þ and Co 2þ , produced almost no response at 10 ¹5 M but, at the higher concentrations tested, they decreased the probability of CCW rotation.…”
Section: Generality Of the Phenomenonmentioning
confidence: 99%
“…In Halobacterium, it has been shown that the cellular concentration of fumarate is under sensory control of the sensory rhodopsin-transducer complexes, and that there is considerable amplification (in terms of fumarate molecules released per activated sensory rhodopsin; Montrone et al 1993). In E. coli, it was shown (1) that motor switching requires fumarate (Barak and Eisenbach 1992), (2) that the probability of motor switching depends on the cellular fumarate concentration, even in the presence of nonphosphorylatable CheY (Montrone et al 1996(Montrone et al , 1998, (3) that the cellular fumarate level regulates motor switching at low temperatures, even in complete absence of CheY (Prasad et al 1998), and (4) that fumarate acts by lowering the free-energy difference between clockwise and counterclockwise states of the motor (Prasad et al 1998). However, the molecular mechanism of how fumarate interacts with the switch complex and the biochemical mechanism of the sensory control of its cytoplasmic concentration in Halobacterium is unclear at present.…”
Section: Discussionmentioning
confidence: 99%